Design and baseline characteristics of a coronary heart disease prospective cohort: two-year experience from the strategy of registry of acute coronary syndrome study (ERICO study) (Clinics, 2013)
OBJECTIVES: To describe the ERICO study (Strategy of Registry of Acute Coronary Syndrome), a prospective cohort to investigate the epidemiology of acute coronary syndrome. METHODS: The ERICO study, which is being performed at a secondary general hospital in São Paulo, Brazil, is enrolling consecutive acute coronary syndrome patients who are 35 years old or older. The sociodemographic information, medical assessments, treatment data and blood samples are collected at admission. After 30 days, the medical history is updated, and additional blood and urinary samples are collected. In addition, a retinography, carotid intima-media thickness, heart rate variability and pulse-wave velocity are performed. Questionnaires about food frequency, physical activity, sleep apnea and depression are also applied. At six months and annually after an acute event, information is collected by telephone. RESULTS: From February 2009 to September 2011, 738 patients with a diagnosis of an acute coronary syndrome were enrolled. Of these, 208 (28.2%) had ST-elevation myocardial infarction (STEMI), 288 (39.0%) had non-ST-elevation myocardial infarction (NSTEMI) and 242 (32.8%) had unstable angina (UA). The mean age was 62.7 years, 58.5% were men and 77.4% had 8 years or less of education. The most common cardiovascular risk factors were hypertension (76%) and sedentarism (73.4%). Only 29.2% had a prior history of coronary heart disease. Compared with the ST-elevation myocardial infarction subgroup, the unstable angina and non-ST-elevation myocardial infarction patients had higher frequencies of hypertension, diabetes, prior coronary heart disease (p